The Discovery of the New World Nature: American Plants in 16th Century Europe - González Bueno, Antonio (Circumscribere International Journal for the History of Science, 2008)
The discovery of the American nature arrived to the Europeans through two ways, separated in time. In a first period, between the initial news on the Columbus discovery and the beginning of the second half of the 16th century, the information spreaded through the descriptions of travellers and chroniclers. In the second, from the 1540s to the beginnings of the 17th century, some texts started to be edited, generally by doctors, traders and gardeners. These works grouped the American plants together, according to strange analogies to similar ones in the Old World. It was only in the 17th century, through the press of Plantino and the pen of Charles L'Ecluse, that appeared the first compilations dedicated exclusively to the new materials proceeding from both Indias.